Farmer registration and development – the SACAU experience in Lesotho and eSwatini - Mashau, Fhumulani (Technical Centre for Agricultural and Rural Cooperation, 2018)
Dispersed smallholder farmers in Sub-Sahara Africa are at risk of social and economic exclusion. Digital innovation and an enabling policy environment can help smallholders to transition out of poverty. The Southern African Confederation of Agricultural Unions (SACAU) considers farmers' organisations to be the key to drive this change.